(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2024)
Electrospinning is a highly adaptable process for producing nanofibers with a wide variety of applications. The resulting fibers are recognized for their biocompatibility, exceptional surface-to-volume ratios, porosity, and adjustable composition properties, making them promising scaffolds for tissue engineering. Previous research already demonstrated successful electrospinning of cellulose acetate. However, these studies used N,N-dimethylformamide (DMF) as a solvent, a substance linked to carcinogenic and mutagenic effects. Therefore, a less toxic solvent system consisting of acetone and dimethyl sulfoxide (DMSO) was used in this study. The investigation focuses on the electrospinning process using cellulose acetate (CA). Initially, the appropriate solvent system substituting acetone/DMF was identified by comparing rheological measurements of different acetone/DMSO compositions with a 3:1 acetone/DMF solvent system described in the literature at constant polymer concentration. With the appropriate acetone/DMSO composition found, various CA solutions with polymer concentration ranging from 12% to 16% (w/v) were investigated. The surface tension was measured via a tensiometer and the morphology and diameter distribution of the electrospun fibers were analyzed using scanning electron microscopy (SEM). Furthermore, the wettability of the electrospun meshes were determined through contact angle measurements. Defect-free fibers are achieved at all polymer concentrations exhibiting uniform morphology and diameters in the nanometer range, indicating the successful fabrication of CA nanofibers. The contact angle measurements showed hydrophilic behavior on all investigated meshes. This study provides valuable insights into the fabrication of CA electrospun fibers which hold promise for various applications, including biomedical scaffolds, scaffolds for cultured meat, filtration membranes and food packaging materials.